2020
DOI: 10.3390/ijms21186942
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Ceramic Bone Scaffolds with Variable Pore Architectures

Abstract: This study evaluated the mechanical properties and bone regeneration ability of 3D-printed pure hydroxyapatite (HA)/tricalcium phosphate (TCP) pure ceramic scaffolds with variable pore architectures. A digital light processing (DLP) 3D printer was used to construct block-type scaffolds containing only HA and TCP after the polymer binder was completely removed by heat treatment. The compressive strength and porosity of the blocks with various structures were measured; scaffolds with different pore sizes were im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 52 publications
(58 reference statements)
0
48
2
2
Order By: Relevance
“…Thus, there is great demand for 3D printing technology; many studies have been published concerning 3D printing technology. Although the evidence regarding 3D-printed alloplastic block bone grafts for ridge augmentation is currently limited to animal studies, the concept is very promising [ 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is great demand for 3D printing technology; many studies have been published concerning 3D printing technology. Although the evidence regarding 3D-printed alloplastic block bone grafts for ridge augmentation is currently limited to animal studies, the concept is very promising [ 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of micropores increase in the surface area of biomaterials while micropore structures have been demonstrated to enhance material resorption and boost osteoinduction (Davison et al, 2014;Rustom et al, 2019). Open and interconnected macropores are not only useful for cell migration and blood vessel formation, but also essential for the diffusion of nutrients, waste and pro-osteogenic factors (Loh and Choong, 2013;Lim et al, 2020). Therefore, porosity not only allows biomaterials to absorb growth factors, but also controls the complex interaction between bone materials and pro-osteogenic factors (e.g., bone morphogenetic proteins).…”
Section: The Influence Of Physical Properties Of Beta-tricalcium Phosphate On Osteogenesismentioning
confidence: 99%
“…As for the pore size, the HA-based 3D printed scaffolds with 1.4 mm and 1.2 mm pore sizes can promote bone regeneration at 4 weeks in rabbit calvarial defects while decreasing the mechanical strength, compared with those scaffolds with 0.8 mm and 1.0 mm pore sizes. However, the effect of pore size on bone regeneration was diminished as time went on to 8 weeks ( Figure 3 c) [ 35 ]. Future research is required to explore better methods to accurately determine the topography of nHA-based 3D printing scaffolds.…”
Section: Nano Hydroxyapatitesmentioning
confidence: 99%
“…( b ) Radiographic analysis showed that 3D hydroxyapatite/extracellular matrix (HA/ECM) composites promoted bone regeneration in rat calvarial defects after 12 weeks [ 34 ]. ( c ) Both radiographic and histological evaluations exhibited more new bone formation for 3D printed nHA-based scaffolds with higher pore size only at 4 weeks [ 35 ]. *: p < 0.05, **: p < 0.01, ***: p < 0.001.…”
Section: Figurementioning
confidence: 99%